2018
DOI: 10.1242/bio.033175
|View full text |Cite
|
Sign up to set email alerts
|

A semi-automatic and quantitative method to evaluate behavioral photosensitivity in animals based on the optomotor response (OMR)

Abstract: The optomotor response (OMR) is a locomotor behavior of animals that is induced by moving repetitive visual stimuli. This characteristic helps animals particularly when stabilizing and maintaining position in schools and herds. Here, we developed a simple but sensitive method for quantifying the OMR using medaka (Oryzias latipes) as a model. This method, which simply requires video-recorded behavior, free tracking software, and a generic spreadsheet program, enables the evaluation of spectral sensitivity by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 31 publications
0
30
1
Order By: Relevance
“…Despite the apparent effects on mate choice, blue light sensitivity of the sws2 mutants was equivalent to that of the wild type (Figure 4). By contrast, in our previous study, an apparent reduction in photopic red light sensitivity could be detected in the lws mutants (Homma et al, 2017;Matsuo et al, 2018). These potentially controversial results are not at all surprising because whereas red light (λ > 740 nm) could only be absorbed by LWSs (λ max = 561-562 nm), blue light tested in this study (λ = 380-500 nm) could likely be absorbed by not only SWS2s (λ max = 405-439 nm) but also the neighboring SWS1 (λ max = 356 nm) and RH2s (λ max = 452-516 nm) (Matsumoto et al, 2006).…”
Section: Apparent Effects Of the Sws2 Mutations On Mate Choice But Nocontrasting
confidence: 85%
See 3 more Smart Citations
“…Despite the apparent effects on mate choice, blue light sensitivity of the sws2 mutants was equivalent to that of the wild type (Figure 4). By contrast, in our previous study, an apparent reduction in photopic red light sensitivity could be detected in the lws mutants (Homma et al, 2017;Matsuo et al, 2018). These potentially controversial results are not at all surprising because whereas red light (λ > 740 nm) could only be absorbed by LWSs (λ max = 561-562 nm), blue light tested in this study (λ = 380-500 nm) could likely be absorbed by not only SWS2s (λ max = 405-439 nm) but also the neighboring SWS1 (λ max = 356 nm) and RH2s (λ max = 452-516 nm) (Matsumoto et al, 2006).…”
Section: Apparent Effects Of the Sws2 Mutations On Mate Choice But Nocontrasting
confidence: 85%
“…These potentially controversial results are not at all surprising because whereas red light (λ > 740 nm) could only be absorbed by LWSs (λ max = 561-562 nm), blue light tested in this study (λ = 380-500 nm) could likely be absorbed by not only SWS2s (λ max = 405-439 nm) but also the neighboring SWS1 (λ max = 356 nm) and RH2s (λ max = 452-516 nm) (Matsumoto et al, 2006). Indeed, we previously found that the wild-type and LWSa/b-knockout medaka could exhibit the OMR at λ ≤ 830 and ≤ 740 nm, respectively (Homma et al, 2017;Matsuo et al, 2018). That is, LWSs and RH2s can absorb and make medaka respond behaviorally to light at wavelengths > 200 nm longer than the λ max .…”
Section: Apparent Effects Of the Sws2 Mutations On Mate Choice But Nomentioning
confidence: 66%
See 2 more Smart Citations
“…In response to global, translational, whole-field motion, larval zebrafish will swim in the direction of perceived motion by generating swimming events called bouts. This reflex is known as the optomotor response (OMR) and can be elicited in both freely swimming and head-restrained zebrafish (Clark, 1981;Orger et al, 2000;Portugues and Engert, 2011), flies (Borst et al, 2010), mice (Matsuo et al, 2018;Shi et al, 2018), and many other species (Dieringer et al, 1982).…”
Section: Introductionmentioning
confidence: 99%